PENGARUH PENERAPAN SISTEM INFORMASI AKUNTANSI, REWARD DAN MOTIVASI KERJA TERHADAP KINERJA PEGAWAI DENGAN BUDAYA ORGANISASI SEBAGAI VARIABEL MODERASI ( Studi pada Kantor BPKAD Kebumen dan BPPKAD Purworejo) - Barbara Gunawan; Yuandini Cella Hermawan (Universitas Mercu Buana Yogyakarta, 2020)
ABSTRACT This study aims to examine the effect of accounting information system application, reward, work motivation on employee performance and also the influence of organizational culture on moderating the application of accounting information systems on employee performance. The objects in this study are the Regional Financial and Asset Management Agency (BPKAD) Kebumen and the Regional Financial and Asset Management Revenue Agency (BPPKAD) Purworejo. This study uses primary data with a survey method. In this study, the sample used was 120 respondents who were selected using a purposive sampling technique. The analytical tools used are Multiple Linear Regression and MRA (Moderating Regression Analysis) with the help of SPSS software. The results of this study indicate that the accounting information system, reward and work motivation have a significant positive effect on employee performance. Furthermore, organizational culture variables are able to moderate the effect of the application of accounting information systems on employee performance. Keywords Accounting Information System, Reward, Work Motivation, Organizational Culture, Employee Performance.